Contribution of soil compositions, harvested times and varieties on chemical fingerprint of Italian and Turkish citrus cultivars. (16th March 2021) - Mottese, Antonio Francesco; Sabatino, Giuseppe; Di Bella, Marcella; Fede, Maria Rita; Parisi, Francesco; Marcianò, Giuseppe; Tripodo, Alessandro; Italiano, Francesco; Dugo, Giacomo; Caridi, Francesco
Summary: This paper aims to define the stability over the time of chemical elemental patterns in some citrus varieties of PGI (Protected Geographical Indication) and not PGI Interdonato and Lunario cultivars coming from Italy and Turkey and to set up a range of markers useful to trace their geographical origin. During the 2015–2017 growing seasons, all fruits were collected and subjected to Inductively Coupled Mass spectrometry (ICP‐MS) analysis, in order to determine the multielemental chemical profiles. The chemical variability was calculated for each element by Multi‐way analysis of variance. The results highlighted how the measured Cr, Ni, Al, K, Fe and Zn levels mainly depend on the soil composition and the fingerprint allow to trace the geographical origins. Moreover, the stepwise linear discriminant analysis (SLDA) has allowed to correctly classify the 100% of lemon pulps provenances, based on Ni, Al, K, Ca and Na contents. Finally, our study demonstrates the role played by harvest years, variety and soils composition whose interaction contributed to define the chemical fingerprints. Abstract : The graphical abstract shows the experimental design procedures, starting from sampling to instrumental investigation up to the statistical treatments used.